Evaluation of the effects of carbon dioxide pneumoperitoneum on abdominal wall wound healing in rats undergoing segmental resection and anastomosis of the left colon - Morais,Pedro Henrique Alves de (2012)
PURPOSE: To evaluate the influence of carbon dioxide pneumoperitoneum on abdominal wall wound healing in rats. METHODS: Eighty rats underwent laparotomy, segmental left colon resection, and anastomosis. The animals were divided into three experimental groups and one control group: EI = pneumoperitoneum for 30 minutes before laparotomy (n=20); EII = pneumoperitoneum for 30 minutes after abdominal closure (n=20); EIII = pneumoperitoneum for 30 minutes before laparotomy and 30 minutes after abdominal closure (n=20); C = control group, without pneumoperitoneum (n=20). In each group, 10 animals were killed 7 days and 10 animals 14 days postoperatively. A segment of the abdominal wall was resected and subjected to tensile strength testing. Another segment of abdominal muscle was used for histopathological analysis; the specimens were fixed in formalin and stained with hematoxylin and eosin. RESULTS: There were no differences in histopathology and tensile strength values among animals in the experimental and control groups 7 or 14 days after surgery. CONCLUSION: Under the present experimental conditions, carbon dioxide pneumoperitoneum did not interfere with abdominal wall wound healing.